Adiponectin Deficiency Enhances Anti-Tumor Immunity of CD8+ T Cells in Rhabdomyosarcoma Through Inhibiting STAT3 Activation - Peng, Jiao; Huang, Haifeng; Huan, Qiuchan; Liao, Chenghui; Guo, Zebin; Hu, Die; Shen, Xiangchun; Xiao, Haitao (Frontiers in Oncology, 2022)
Restoring the tumor-killing function of CD8+ T cells in the tumor microenvironment is an important strategy for cancer immunotherapy. Our previous study indicated that adiponectin (APN) deficiency reprogramed tumor-associated macrophages into an M1-like phenotype to inhibit rhabdomyosarcoma growth. However, whether APN can directly regulate the anti-tumor activity of CD8+ T cells remains unknown. In the present study, our results showed that exogenous APN inhibited in vitro CD8+ T cell migration as well as cytokines IFN-γ and TNF-α production. APN deficiency in vivo strengthened CD8+ T cell activation and cytotoxicity to restrain rhabdomyosarcoma, evidenced by an increase in the expression of IFN-γ and perforin in CD8+ T cells and the frequency of CD8+IFN-γ+ T cells in the spleen and lymph nodes, as well as increasing cytokine production of IFN-γ, perforin, TNF-α, and decreasing cytokine production of IL-10 in the serum. Mechanistically, STAT3 was identified as a target of APN in negatively regulating the anti-tumor activity of CD8+ T cells. In vivo, a STAT3 inhibitor remarkably increased CD8+ as well as CD8+IFN-γ+ T cells in the spleen and lymph nodes. Taken together, we substantiated that APN deficiency directly maintains the activation of CD8+ T cells to inhibit rhabdomyosarcoma growth by suppressing STAT3 activation, indicating a promising APN-based therapy for the treatment of rhabdomyosarcoma.